Functional mesoporous silica nanoparticles for photothermal-controlled drug delivery in vivo - Yan, Hong (2013)
Release me! A new class of photothermal-responsive [2]rotaxane-appended mesoporous silica nanoparticles (MSNPs) was developed. Remote-controlled movement of the α-cyclodextrin ring (green) upon trans–cis isomerization of the azobenzene axle (red) enables the loading and release of drugs on demand (see scheme). Curcumin-loaded MSNPs were shown to release curcumin into zebrafish larvae upon treatment with visible light or heat.